Kemampuan Literasi Matematis Siswa dalam Menyelesaikan Soal Sistem Persamaan Linear Satu Variabel Konteks Parkir Kendaraan - Nazwa Khairunnisa Maharani; Feri Tiona Pasaribu; Syamsir Sainuddin (Universitas Ma'arif Lampung, 2025)
Several previous studies have widely discussed students’ mathematical literacy; however, research that specifically analyzes junior high school students’ mathematical literacy in the topic of Linear Equations in One Variable through contextual problems remains limited. Therefore, this study aims to describe the mathematical literacy abilities of junior high school students in solving contextual problems related to the System of Linear Equations in One Variable. This study employed a qualitative research method involving 33 eighth-grade students of class VIII-I at SMP Negeri 6 Kota Jambi with diverse ability levels. The research instruments consisted of contextual essay tests, interviews, and documentation of students’ written responses. The test items were validated by experts and designed to reflect real-life situations. The results indicate that students’ mathematical literacy skills are generally low, with the majority of students classified in the low category. Students experienced difficulties in understanding information presented in the problems, formulating mathematical models, and interpreting as well as concluding the solutions. Analysis based on mathematical literacy indicators shows that only a small proportion of students were able to fulfill all three indicators comprehensively. These findings suggest that students have not yet met the demands of solving contextual problems mathematically. The results of this study may serve as a basis for developing more contextual and applicative mathematics literacy–based learning to improve the quality of mathematics education at the junior high school level.